Rancang Bangun Sistem Informasi Pengelolaan Aktivitas Penghimpunan Dana Berbasis Web Studi Kasus Yayasan Arrisalah - Ari Wahyono; Wisnu Sanjaya (JITU : Journal Informatic Technology And Communication, 2022)
One of the work units of the Arrisalah Foundation is engaged in social activities that collect funds from the community. Excel application is used in the process of work activities. The use of excel is no longer relevant because of the increasing amount of data, and it is very dependent on the administrator team's thoroughness, precision, skill, and expertise. Searching data and recapitulating reports is also a problem because it takes a long time to process, so an automation process is needed to make work faster and more accurate. This study aims to build a web-based information system using the waterfall model to overcome these problems. The system design process uses UML, and the information system is made using the PHP programming language and Mysql database. The results achieved in this study are that the information system has been successfully created and can automate reports so that the reporting process is faster and easier